2000
DOI: 10.1034/j.1600-0420.2000.078002196.x
|View full text |Cite
|
Sign up to set email alerts
|

Peribulbar anesthesia and sub‐Tenon injection for vitreoretinal surgery: 300 cases

Abstract: ABSTRACT. Background and objectives:We carried out a prospective study in order to evaluate the efficacy and safety of peribulbar anaesthesia supplemented by a sub-Tenon injection in case of inadequate analgesia during vitreoretinal surgery. Methods: We performed 300 consecutive vitreoretinal procedures. Patients received a mean volume of 17∫4.5 ml of a mixture of etidocaine 1%, bupivacaine 0.50% and hyaluronidase (25 UI/ml). Supplementation was represented by a sub-Tenon infiltration of lidocaine 2% (2 or 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…However, more recent published data show strong evidence of the effectiveness of local anaesthesia in intraoperative comfort and in controlling postoperative pain. 7,9,[18][19][20] Isernhagen's results were also skewed with 58% of eyes having previous retinal surgery.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, more recent published data show strong evidence of the effectiveness of local anaesthesia in intraoperative comfort and in controlling postoperative pain. 7,9,[18][19][20] Isernhagen's results were also skewed with 58% of eyes having previous retinal surgery.…”
Section: Discussionmentioning
confidence: 95%
“…There are several other reports that support our findings of reduced pain and patient satisfaction for local anaesthesia. 7,9,[18][19][20] In September 2004, the in patient facility was withdrawn from the dedicated eye unit at King Edward VII Hospital, Windsor. This study was designed to identify the intervention necessary during in-patient stay and the feasibility of providing day-case surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The reluctance to use local anaesthesia alone for vitreoretinal surgery may stem from the longer, more unpredictable and uncomfortable nature of such surgery [4]. Surgical dissatisfaction because of insufficient akinesia resulting from partial blockade [5] and patient discomfort during prolonged surgery involving scleral buckling are further limitations to the use of local anaesthesia alone. The combination of general anaesthesia and peribulbar anaesthesia may reduce these drawbacks [6].…”
mentioning
confidence: 99%
“…A variety of methods have been described. [8][9][10][11][12][13][14][15][16][17] Advantages of LA over GA include more rapid patient recovery; however also there are some procedures where having an awake patient who is able to cooperate and follow instructions can be helpful. In PRP treatment, the retention of motility such that the patient is able to move the eye around on request leads to an easier view of the peripheral retina with less need for indenting, less conjunctival trauma, and more complete peripheral treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Local anaesthesia has replaced general anaesthesia as it is well tolerated by patients and allows rapid postoperative recovery. [8][9][10][11][12][13][14][15][16] Several local anaesthetic techniques for VR have been used and we have previously reported results using the anterior intraconal technique first described by Wong et al 17 Several authors comment that a potential problem with this technique was that total akinesia was difficult to achieve, which may make perioperative complications more likely. In our hands, however, we found that the intraconal block gave an akinetic block in the majority of cases.…”
Section: Introductionmentioning
confidence: 99%